A cross-sectional study on the respiratory status of the steel foundry workers of West Bengal (Funded Work) - SAMIR KUMAR PAINE; MOUMITA SETT; NITIS CHANDRA SAHA; SUBHASHIS SAHU (International Journal of Pharma and Bio Sciences, 2017)
Steel foundry workers are at risk in terms of respiratory disorders including asthma, Chronic Obstructive Pulmonary Disease (COPD) and even lung cancers. However, a cross-sectional study was done on 899 male foundry workers engaged in manufacturing different parts of locomotives in the district of Burdwan, West Bengal, India. There is dearth of data regarding the pulmonary status and the prevalence of respiratory disorders among these groups of workers in West Bengal.Physical parameters and spirometry were performed on these workers and they were classified as per smokers (Group I) and non smokers (Group II). Also status of the working environment was collected and produced by the certified agency of the authority (steel foundry factory) concerned. From the data analyses it was seen that both the group of workers were prone to suffer from respiratory problems with aggravating conditions of the group II workers, though the working time were 8 hours in both the groups. It was evident from the results obtained from Forced Vital capacity (FVC) (I-2.14±0.44, II-2.52±0.23; p<0.0001), Forced Expiratory Volume in 1stsec (FEV1)(I- 1.92±0.38, II- 2.32±0.17; p<0.0001) and FEV1/FVC (I- 88.86±0.19, II-88.94±4.27; NS). They may have the prevalence of occupational asthma or COPD; though the working environmental results produced by the factory authority were shown to be under permissible exposure limits. Other signs and symptoms include wheezing, coughing, shortness of breath etc. However, long-term follow-up study is needed along with clinical trials with bronchodilators. A new recommendation for the permissible exposure limits in this case must be set up. Additional reports of imaging will be an added value. The workers did not use any protective gears so must be encouraged to wear Personal Protective Devices (PPDs). All these lacunae will be hopefully filled up in the future studies.